PARADIGMA SISTEM DESENTRALISASI PENDIDIKAN SECARA HOLISTIK - Syahril Chaniago (Jurnal Ilmiah Econosains, 2013)
ABSTRACTPlanned implementation of regional autonomy has been started since enacted in 2001 which refers again to the latest two laws, namely: Law No. 32 of 2004 on Regional Government and the number 33 of 2004 on Fiscal Balance- Regional Center. Autonomy with the affairs of the Authority shall be to all services delivered indirectly to the district / city and province with the General Allocation Fund (DAU), whereas dealings with the option Special Allocation Fund (DAK). Centralized system changes pemedntahan be desentralisfik is a new paradigm that became the basis of systematic thinking, especially in terms of the national policy on education (Education).Keywords: regional autonomy, regional government, education